The Principal’s Role in the Implementation of 7KAIH (Kebiasaan Anak Indonesia Hebat) Program - Azizah, Durotul; Soedjono, Soedjono; Kusumaningsih, Widya (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to comprehensively describe the principal's role in implementing the 7KAIH program at SMP Salafiyah Pekalongan. 7KAIH is a strategic movement to build Indonesia’s 2045 golden generation through the development of positive character and life skills. The study focuses on how the principal plans, organizes, implements, and evaluates the program to ensure its effective and consistent implementation within the school environment. The 7KAIH program is implemented not only as a routine activity but also as a strategic effort to strengthen character education and build positive habits among students in their daily lives. The theoretical framework of this study is based on the POAC (Planning, Organizing, Actuating, and Controlling) management theory proposed by Terry, Fayol, Robbins, and Coulter, as well as theories of educational leadership and character education. This study employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation. Data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that the principal carries out the planning function by integrating the 7KAIH program into the school's vision, annual program, and school culture. The organizing function is carried out by forming an implementation team and providing a clear division of tasks. The driving function is implemented through providing role models, motivation, and intensive communication with teachers, students, and parents, while the controlling function is carried out through journal-based monitoring and periodic evaluation.